Hubungan Pengetahuan dan Akses Informasi dalam Pemanfaatan Terapi Komplementer untuk Mengurangi Mual Muntah pada Ibu Hamil Trimester I di Puskesmas Putri Ayu - Tiwi, Laida Sanilpa; Nurbaiti, Nurbaiti; Perwitasari, Tuhu (Jurnal Akademika Baiturrahim Jambi, 2025)
Nausea and vomiting are common symptoms in the first trimester of pregnancy. The hormones estrogen and progesterone cause excessive stomach acid production, causing nausea and vomiting, especially in the morning, known as morning sickness. Psychologically, nausea and vomiting during pregnancy affect 80% of pregnant women, resulting in a decreased appetite. In this condition, mothers must continue to eat to ensure the fetus's growth and development. This study aims to determine the relationship between knowledge and access to information in the use of complementary therapies to reduce nausea and vomiting in first-trimester pregnant women. This study was conducted from February 3 to June 20, 2024. Data were collected using a questionnaire. The type of research used was a cross-sectional analysis approach. The population in this study were first-trimester pregnant women with a sample of 18 respondents using the accidental sampling method. Data were analyzed using univariate and bivariate methods using the chi-square statistical test. The results showed that most respondents had good knowledge (38.8%) and good access to information (55.6%). The results of the Chi-Square test showed a significant relationship between knowledge and the use of ginger tea (p-value 0.001), and a significant relationship between access to information and the use of ginger tea (p-value 0.002). It is hoped that health workers will continue to play an active role in introducing complementary therapies to reduce nausea and vomiting in pregnant women in the first trimester by providing accurate information so that they can apply them safely and effectively, and the need for anti-nausea medication can be minimized.